2016
DOI: 10.1007/7854_2016_39
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Actions of Synthetic Cathinones on Monoamine Transporters

Abstract: Products containing psychoactive synthetic cathinones, such as mephedrone and 3,4-methylenedioxypyrovalerone (MDPV) are prevalent in our society. Synthetic cathinones are structurally similar to methamphetamine, and numerous synthetics have biological activity at dopamine, serotonin, and norepinephrine transporters. Importantly, monoamine transporters co-transport sodium ions along with their substrate, and movement of substrates and ions through the transporter can generate measurable ionic currents. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 105 publications
3
13
0
Order By: Relevance
“…By using the TEVC technique in X. laevis oocytes overexpressing monoamine transporters, we previously showed that transportable substrates produce large Na +dependent inward currents, whereas nontransported inhibitors do not. In fact, transporter inhibitors evoke an apparent outward current because of blockade of the endogenous transporter 'leak' current (Cameron et al, 2013;Rodriguez-Menchaca et al, 2012;Solis, 2017;Solis et al, 2012). As expected, compounds eliciting maximal release efficacy in synaptosomes (eg, N-methyl 4-MA at DAT) also produced large inward currents through hDAT.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…By using the TEVC technique in X. laevis oocytes overexpressing monoamine transporters, we previously showed that transportable substrates produce large Na +dependent inward currents, whereas nontransported inhibitors do not. In fact, transporter inhibitors evoke an apparent outward current because of blockade of the endogenous transporter 'leak' current (Cameron et al, 2013;Rodriguez-Menchaca et al, 2012;Solis, 2017;Solis et al, 2012). As expected, compounds eliciting maximal release efficacy in synaptosomes (eg, N-methyl 4-MA at DAT) also produced large inward currents through hDAT.…”
Section: Discussionsupporting
confidence: 56%
“…We evaluated the electrophysiological effect of the test compounds at hDAT and hSERT in X. laevis oocytes expressing these transporters and voltage-clamped to -60 mV. As noted previously, transporter substrates induce inward depolarizing currents whereas inhibitors induce outward currents (Solis, 2017;Solis et al, 2012). Figure 2 shows the effects of 4-MA analogs on transporter-mediated currents.…”
Section: Transporter-mediated Ionic Currents In Transporter-expressinmentioning
confidence: 94%
See 1 more Smart Citation
“…All three drugs can traverse monoamine transporters and trigger a series of intracellular events that promote monoamine neurotransmitter release [36]. As a group, these drugs are sometimes called “transporter substrates,” because like the endogenous neurotransmitters, they can pass from the extracellular space through the transporter channel to the intracellular space.…”
Section: Amphetamine Mdma and Fenfluramine As Prototype Monoaminementioning
confidence: 99%
“…Limited mechanistic data for dimethylone, dibutylone, and N-ethylpentylone exist; however, data for their mono-and methyl-substituted counterparts are abundant. Dimethylone acted as an uptake inhibitor at both the dopamine transporter (DAT) and serotonin transporter (SERT) in one study (Solis, 2017), but only at DAT in another (Eshleman et al, 2018), and did not produce monoamine release (Eshleman et al, 2018). Dibutylone was 32-fold selective at the DAT over the norepinephrine transporter (NET) for blocking uptake, produced no uptake effects at the SERT, and did not produce monoamine release (Eshleman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%